Less Subjectivity in Setting Cut Scores: A Novel Approach - Atanas, Jean Pierre (Journal of Education and Vocational Research, 2013)
Recently, standard-setting cut scores and assessment techniques became of major concerns for many organizational institutions worldwide. A cut score separates one performance level from another. It differentiates between those who pass and those who fail. They may vary according to the recommendations of policy makers and stakeholders. Passing scores were suggested by many methods on numerous types of tests: certification tests and educational tests. Most of these standard setting methods rely on panelists’ subjectivity in ordering items by level of difficulty. This paper presents a simple approach to assessments by minimizing considerably panelists’ subjectivity. Items are classified in levels of difficulties rather than in an increasing order in most of the standard methods. This novel approach respond to three main criteria: practicality, wide range of applicability and maximum agreement with the empirical data. Provisional and operational cut scores were derived and discussed.